2018
DOI: 10.1186/s13024-018-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

A brain-penetrant triazolopyrimidine enhances microtubule-stability, reduces axonal dysfunction and decreases tau pathology in a mouse tauopathy model

Abstract: BackgroundAlzheimer’s disease (AD) and related tauopathies are neurodegenerative diseases that are characterized by the presence of insoluble inclusions of the protein tau within brain neurons and often glia. Tau is normally found associated with axonal microtubules (MTs) in the brain, and in tauopathies this MT binding is diminished due to tau hyperphosphorylation. As MTs play a critical role in the movement of cellular constituents within neurons via axonal transport, it is likely that the dissociation of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 72 publications
(137 reference statements)
3
67
0
Order By: Relevance
“…The study results further emphasize that MT abnormalities appear to be a key feature of AD, as well as other neurodegenerative diseases 31 . Importantly, small molecule MT‐stabilizing agents such as 51657 can reduce AD‐like pathology and confer neuronal benefits in mouse models with only tau pathology 21,22,28,36,39 or in mice with only Aβ pathology, as demonstrated here. MT‐stabilizing compounds are thus unique in being able to independently affect the two key pathologies found in the AD brain.…”
Section: Narrativesupporting
confidence: 73%
See 2 more Smart Citations
“…The study results further emphasize that MT abnormalities appear to be a key feature of AD, as well as other neurodegenerative diseases 31 . Importantly, small molecule MT‐stabilizing agents such as 51657 can reduce AD‐like pathology and confer neuronal benefits in mouse models with only tau pathology 21,22,28,36,39 or in mice with only Aβ pathology, as demonstrated here. MT‐stabilizing compounds are thus unique in being able to independently affect the two key pathologies found in the AD brain.…”
Section: Narrativesupporting
confidence: 73%
“…Moreover, these low doses of epothilone D did not lead to changes in blood cell counts, including neutrophils, 28 which is a leading side effect when MT‐stabilizing drugs are used in oncology settings 44,45 . Similarly, the doses of 51657 that led to improvements in tau Tg mice, and here in Tg Aβ plaque mice, did not affect neutrophil or other blood cell counts 39 . Finally, the doses of epothilone D used in the short Phase 1b trial, which were similar to those used in Tg mouse studies when scaled for species, did not result in adverse events 43 .…”
Section: Narrativementioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, the current study found that metformin contributed to increased phospho-tau in both ApoE3-TR mice and ApoE4-TR mice. Previous studies reported that metformin decreases phospho-tau or promotes its aggregation in young or tauopathy mice (56,57). The inconsistency may be due to the fact that the current study probed into phospho-tau in old ApoE-TR mice under a chronic metformin treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Hyperphosphorylated tau plays an important role in the formation of neurofibrillary tangles in brains of AD patients and related tauopathies (56,57). Several studies suggest that ApoE4 increases the levels of phospho-tau (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%